Pressure Methods for Primary Hemorrhage Control: A Randomized Crossover Trial (International Journal of First Aid Education)
Background: The importance of hemorrhage control in traumatic injury has been highlighted by the 2015 Stop the Bleed federal campaign in the United States and subsequent development of modular bleeding control courses offered by organizations such as the American Red Cross (https://www.dhs.gov/stopthebleed). However, the scientific evidence regarding the best methods and mechanisms of applying direct manual pressure to stop hemorrhage is lacking to inform first aid education skill development. Hypothesis: The purpose of this tri-phase study is to evaluate the pressure generated when adding increasing layers of gauze dressings and to compare the force generated using different techniques of force application. Additionally, we aimed to measure the pressure generated by a pressure wrap using two commonly used types of bandages in comparison to manual pressure. Methods: In this tri-phase randomized crossover trial of medical personnel, a standardized bleeding simulator with a flat force sensitive resistor on the surface was used to measure force. Participants were randomized to order of pressure with gauze application (10, 20 & 30 layers of 4x4 inch cotton gauze, respectively) and subsequently to three different methods of pressure application: the finger pads of 3 digits of the right hand, 3 fingers of the dominant hand with the opposing hand applying counter pressure, or 3 digits of each of two hands on top of the other. Participants were asked to hold pressure continuously during each application for 10 seconds and all completed each method sequentially. Participants then applied a compression wrap using either an elastic wrap or self-adhesive wrap. Results: Thirty-three participants were enrolled, and all had data available for analysis. Pressure applied with a stack of 10- 4x4 inch gauze pads generated a greater force than with 30 gauze pads [3.20 (95% CI: 2.80-3.59) lbs. of pressure vs 1.58 (95% CI: 1.39-1.77) lbs.]. Two hand pressure application generated a greater force than one hand application [3.75 (95% CI: 3.20-4.30) lbs vs. 3.00 (95% CI: 2.54-3.46) lbs]. Neither pressure wrap technique generated a comparable amount of force to that of manual force. Conclusion: In this simulated model of bleeding, medical personnel generated the most force when a single stack of gauze and when two hands were used to apply pressure over the wound. This study also demonstrated direct manual pressure generated much higher pressures than a pressure dressing. First aid educators may apply results to lessons in describing the thickness of material and need to apply sufficient pressure to stop bleeding.